Magnetic field boosted ferroptosis-like cell death and responsive MRI using hybrid vesicles for cancer immunotherapy - Bo Yu (Nature Portfolio, 2020)
The immune system can eradicate tumours, and several chemotherapy strategies have been reported to augment the immune system. Here, the authors report an exogenous magnetic field triggered strategy to boost Ferroptosis-like death and endow responsive MRI by using a biosafe hybrid core-shell vesicle for cancer therapy.